EFFECT OF CONSUMPTION ON ACCEPTANCE OF VALUE ADDED TAXES ( VAT ) IN INDONESIA DURING 1984-2016 - Juliannisa, Indri Arrafi (AFEBI Economic and Finance Review, 2018)
VAT is a tax component that contributes the most to total tax revenue, this study analyzed the relationship of consumption to VAT receipts, but there are other free control variables such as; the money supply, population, and industrial sector revenues. This study refers to previous research that has been carried out by Harju, Kosonen, and Skans (2018) , entitled about “Firm types, pricesetting strategies, and consumption-tax incidence”. This study uses a Time Series Model, that is : is a forecast of future values based on past values of a variable and past mistakes. Time series models are usually use for forecasting. The research method used is quantitative descriptive, by using the Eviews test tool. Because at the beginning of testing this research experienced problems on the classical assumption test, then to overcome the problem of classical assumption test, the test continues using estimation method Newey-West HAC regression model (heteroscedasticity and autocorrelation consistent) standard error or more often called Newey-West HAC. The results of the study show that consumption as the main independent variable has a significant effect, and the control variable that has influence is the money supply and the industrial sector. the increasing amount of consumption each year can stimulate VAT revenues and economic growth in Indonesia. JEL Classification: H20, H25, H26 Keywords: Consumption, Industrial sector Money Supply, VAT